Representation of language functions in the bilingual brain - Mildner, Vesna (Array, 2001)
Results of clinical and behavioral studies of the cerebral representation of language functions are reviewed. Neurolinguistic organization of the bilingual brain is discussed and recent data obtained in the studies of Croatian-English bilinguals are presented and discussed.